KINETIC STUDY OF CHROMIUM CHROMIUM RECOVERY FROM INDUSTRIAL WASTEWATER. PART 1: ROUGH SYSTEMS - Armijo C., Javier (2003)
They have carried out experiments for the ion exchange reaction between ions Cr2O7 solutions and ion exchange resin in the chloride form. The concentration profile is reported in equivalent amounts of Cr +6 with time, for 0.1, 0.5 and 0.75 gram of resin. The results indicate that longer times are required at 2500 seconds to reduce the concentration to less than 1 ppm of Cr +6 in a volume of 250 ml of solution stirred at 250 rpm, with an initial concentration of 50 ppm and a weight of 0.75 grams resin.